Rebalancing commercial and public interests in prioritizing biomedical, social and environmental aspects of health through defining and managing conflicts of interest - Redman, Barbara K. (Frontiers in Medicine, 2023)
Abstract Biomedical research is intended to benefit human beings and their health. Toward that end, scientific norms involve examining and criticizing the work of others and prioritizing questions that should be studied. Yet, in areas of health research where industry is active, it has often utilized well-honed strategies aimed at evading scientific standards and at dominating the research agenda, largely through its financial support and lack of transparency of its research practices. These tactics have now been documented to uniformly support industry products. Commercial entities are aided in this pursuit by public policy that has significantly embedded commercial interests and agendas into federal research funding and infrastructure. Therefore, to understand the resulting landscape and its effect on priority in health research agendas, traditional definitions of individual conflicts of interest (COI) and the less well developed institutional COI must be supplemented by a new construct of structural COI, largely operating as intellectual monopolies, in support of industry. These arrangements often result in financial and reputational resources that assure dominance of commercial priorities in research agendas, crowding out any other interests and ignoring justified returns to the public from investment of its tax dollars. There is no sustained attention to mechanisms by which public interests can be heard, normative issues raised, and then balanced with commercial interests which are transparently reported. Focus on research supporting approval of commercial products ignores social and environmental determinants of health. Commercial bias can invalidate regulatory research protections through obscuring valid risk–benefit ratios considered by IRBs.